Effects of translational and rotational degrees of freedom on properties of the Mercedes–Benz water model - Urbic, T. (J Chem Phys, 2017)
Non–equilibrium Monte Carlo and molecular dynamics simulations are used to study the effect of translational and rotational degrees of freedom on the structural and thermodynamic properties of the simple Mercedes–Benz water model. We establish a non–equilibrium steady state where rotational and translational temperatures can be tuned. We separately show that Monte Carlo simulations can be used to study non-equilibrium properties if sampling is performed correctly. By holding one of the temperatures constant and varying the other one, we investigate the effect of faster motion in the corresponding degrees of freedom on the properties of the simple water model. In particular, the situation where the rotational temperature exceeded the translational one is mimicking the effects of microwaves on the water model. A decrease of rotational temperature leads to the higher structural order while an increase causes the structure to be more Lennard–Jones fluid like.